Investigation of volatile constituents of beer, using resin adsorption and GC/MS, and correlation of 2-(3H)-benzoxazolone with wheat malt - Pothou, E.a; Melliou, E.b; Skaltsounis, A.-L.b; Liouni, M.c; Magiatis, P.b (Journal of the American Society of Brewing Chemists, 2013)
The volatile constituents of 22 samples of commercial beers (lager, ale, and lambic) were isolated using adsorption resin XAD-4 and analyzed by gas chromatography, using mass-spectrometric detection. The presence of 63 volatile components was examined in each sample. Major common compounds identified in all of the studied samples were 2-methylpropanol (0.77-12.9%), 3-methylbutanol (32.0-55.5%), phenylethanol (18.7- 58.8%), and tyrosol (0.69-5.82%), expressed as TIC percent. Most other components were found in various concentrations but their presence was not uniformly distributed in all the studied beers. One of the minor volatile compounds, 2-(3H)-benzoxazolone, was found only in beers made with wheat malt. Additionally, for the first time, tryptophol acetate was identified as beer constituent. Finally, principal component analysis of the volatile compounds was able to discriminate the group of beers containing wheat. © 2013 American Society of Brewing Chemists, Inc.